Political Cataclysms at the Start of the Century and the Future of the International Relations System - A. V. Korobkov (Vestnik MGIMO-Universiteta)
Abstract: Crises in Ukraine and the Middle East indicate the existence of deep shifts in the global international relations system. These shifts are much more serious than the widely discussed erosion of the US international monopoly and are related to the global transfer of the world economic and political power center from North Atlantic to the Pacific Basin. Thus quickly collapsing is the world Eurocentric system that has ruled the world since the end of the Fifteenth century. Meanwhile, the Western, and especially the European elites refuse to recognize the scale and the potential consequences of these processes. In particular, their actions are pushing Russia towards China. Retaining stability of the international system would require the recognition by the Global North of the reality of these changes, the return to the acceptance of the state sovereignty concept, and the abandonment of attempts to impose its will on the others under.